ECOLOGICAL DA’WAH UNDER EXTRACTIVE CAPITALISM: A CRITICAL READING OF RELIGIOUS NARRATIVES IN THE ENVIRONMENTAL CRISIS: (META-ANALYSIS) - Muhamad Bisri Mustofa; Siti Wuryan; Hengky Ahmad Rihal; Azhar Jaafar; Faizal; Bahri Ghozali (Universitas Islam Negeri Mataram, 2025)
This study analyzes the construction of Islamic ecological da'wah in extractive capitalism and highlights the limitations of the critical literature in linking ecological da'wah to global economic structures. The research method used Systematic Literature Review (SLR). The results of the study show that ecological da'wah is constructed through Islamic values, environmental ethics, and conservation practices that emphasize changes in human consciousness and behavior. There has been a shift in research focus from an anthropocentric approach to eco-theology and environmental conservation. Most ecological da'wah discourses still operate on a cultural and spiritual level, without explicitly challenging the logic and structure of extractive capitalism as the main cause of environmental degradation.